(untitled) (Simbiótica. Revista Eletrônica, 2013)
Abstract: The present paper provides an overview of the functions of the morphological focus marker hop in the grammar of Wichí, a Mataco-Mataguayan language spoken in the North of Argentina and the South of Bolivia. Basing the analysis on the corpus which I have compiled from the existing research which has been published on the language so far, we can conclude that the focus marker hop can but does not have to be used for the focusing of the subject, object, predicate, adverbial as well as on entire dependent clauses in the language. The focus marker hop can express both the informational focus as well as the contrastive focus. In the case of predicate focusing the verum-focus can also be marked and the focus marker can scope over the complex predicate. Key words: Wichí; Languages of America; Information structure; Focus marker. Resumo: O presente artigo fornece uma visão geral das funções do marcador morfológico hop na gramática de Wichí, uma linguagem Mataco-Mataguayan falada no norte da Argentina e no sul da Bolívia. Com base na análise do corpus que compilamos a partir das pesquisas existentes e publicadas sobre a língua até agora, podemos concluir que o marcador de foco hop pode, mas não tem que, necessariamente, ser usado para o foco no sujeito, objeto, predicado, advérbio, bem como nas cláusulas inteiramente dependentes na língua. O marcador de foco hop pode expressar tanto o foco informacional quanto o foco contrastante. No caso do predicado com foco no verum-foco, também pode ser marcado e o marcador de foco sobre o predicado complexo pode se estender. Palavras-chave: Wichí; idiomas da América; estrutura de informação; marcador de foco. Resumen: El articulo presentado ofrece una descripción general de las funciones del marcador morfológico de foco hop en la gramática de la lengua Wichí, hablada en el Norte de Argentina y el Sur de Bolivia. El presente análisis hecho a base del corpus formado de investigaciones publicadas sobre la lengua revela que el marcador de foco hop puede ser utilizado para focalización tanto de sujeto, objeto, predicado, complemento circunstancial, como de oración subordinada en la lengua. El marcador de foco hop puede expresar el foco informacional y el foco contrastivo. En el caso de focalización verbal puede ser marcado el verum foco y el scopus del marcador puede extenderse sobre el predicado complejo. Palabras claves: Wichí; lenguas de America; estructura informacional; marcador de foco.